Effect of acidification and thermal treatment on quality characteristics of high‐moisture laver (Porphyra spp.). Issue 8 (22nd May 2022) - Ge, Mengmeng; Shen, Jiandong; Liu, Cikun; Xia, Wenshui; Xu, Yanshun
Abstract: Effects of two thermal treatments (sterilization at 118°C and pasteurization at 90°C) and acidification on the color, texture, chemical composition, and microstructure of high‐moisture laver were investigated. Results showed that the reddish‐purple of laver faded to varying degrees after heating due to rapid degradation of phycoerythrin. With increasing heating time, the a * value gradually decreased accompanied by the increase in b * value, and the color changed to yellow‐green. Besides, the hardness and toughness gradually decreased, while the adhesiveness increased. Microstructure and soluble sugar results indicated that the cell tissue of the laver was destroyed after intensive heating. Compared to sterilization, laver subjected to pasteurization at 90°C exhibited better texture and color. Intensive thermal processing accelerated quality deterioration as evidenced by pigment degradation, cell rupture, and increase in soluble substances. The combination of acidification (pH < 4.6) with mild heat treatment contributed to better quality retention of ready‐to‐eat lavers with higher moisture. Practical applications: Since most of the existing laver products in the market are dry, the development of high‐quality wet laver products has attracted attention. However, due to the extremely thin leaves and soft texture, the color and texture of laver are prone to deterioration during the heat sterilization process. Understanding the quality changes of laver under typical sterilization conditions is conducive for exploring solutions. The present study clarifies the effects of heat treatment and acidification on the characteristics of high‐moisture laver, which serves as a foundation for the future development of instant wet laver products that can meet both safety and palatability, and provides theoretical guidance for the seaweed processing industry.